Experimental investigation of gliding arc plasma fuel injector for ignition and extinction performance improvement. (1st February 2019) - Lin, Bingxuan; Wu, Yun; Zhu, Yifei; Song, Feilong; Bian, Dongliang
Graphical abstract: Highlights: A gliding arc plasma fuel injector is proposed. The ignition limit and lean blow-out limit were largely extended. The drop size of kerosene spray decreases. Several light hydrocarbons were generated. Abstract: Flame extinction at high-altitude is one of the serious safety problems for aero-engines. The low pressure and temperature at high-altitude make it difficult to relight after extinction. Plasma-assisted combustion has been widely investigated in aerospace propulsion systems, while the mechanism is still not clear. In this study, a novel gliding arc plasma fuel injector using alternating current discharge is proposed to obtain reliable altitude relight performance and wider lean blow-out limits. The ignition and extinction experiments of gliding arc plasma fuel injector using 5 °C and −30 °C kerosene (RP-3) were conducted. A thin and string-like gliding arc plasma column was observed with repeating phases of breakdown between the fuel atomizer and venturi nozzle, extension with rotating airflow and column quenching. The optical emission spectroscopy of gliding arc plasma in gliding arc plasma fuel injector indicated the significant thermal effect caused by the arc column. Using gliding arc plasma fuel injector, the ignition limit was greatly extended, almost to the lean blow-out limits for the low temperature fuel. Low temperature and low injection pressure lead to much larger droplets and irregular injection cone. Influenced by heating and hydrodynamic effect of gliding arc plasma, the drop size at −30 °C kerosene spray decreases from around 150 μm to 30 μm, which is a main reason for ignition range extension. The equivalence ratios of lean blow-out were extended by up to 48% and 47% using 5 °C and −30 °C kerosene, respectively. Several light hydrocarbons, such as CH4 (1.26 SLM), C2 H4 (1.31 SLM) and C2 H2 (2.30 SLM) with larger laminar flame propagation velocity, were detected as reforming products. Both heating and reforming effects contribute to the lean blow-out limit extension. The residence time of kerosene sprays in gliding arc plasma fuel injector is the determining factor for conversion capability.